All the lost places - Dykes, Amanda (Bethany House, a division of Baker Publishing Group, 2022)
"Discovered floating in a basket along the canals of Venice, Sebastien Trovato wrestles with questions of his origins. Decades later, on an assignment to translate a rare book, Daniel Goodman finds himself embroiled in a web of secrets carefully kept within the ancient city and in the mystery of the man whose story the book does not finish: Sebastien"--